Wasted opportunities - Nur Syahidah Abdul Rahim (2014)
What happens when we are to get rid of the things that we no longer want? Why do we throw them and what happens to them after they are being disposed? Where do they go? These are some of the questions that I would ask myself when I see a large amount of waste being disposed.